2016
DOI: 10.1097/opx.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Reduced Accommodative Lag and Myopia Progression

Abstract: This study showed no relationship between lag of accommodation and rate of myopia progression in children with progressing myopia. Different ethnic groups may respond differently to the same size of hyperopic blur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…There appears to be no relationship between the lag of accommodation and myopia progression. 14,26 It is not clear why under-correction would accelerate myopic progression, but study findings suggest that any malfunction of the sign detection mechanism in emmetropisation can cause eye growth. 12 Progressing myopes have large accommodative lags, micro-fluctuations and an increased depth of focus, compared to non-myopes, but similar blur detection thresholds.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…There appears to be no relationship between the lag of accommodation and myopia progression. 14,26 It is not clear why under-correction would accelerate myopic progression, but study findings suggest that any malfunction of the sign detection mechanism in emmetropisation can cause eye growth. 12 Progressing myopes have large accommodative lags, micro-fluctuations and an increased depth of focus, compared to non-myopes, but similar blur detection thresholds.…”
Section: Discussionmentioning
confidence: 88%
“…Koomson et al conducted a two‐year single masked randomised controlled trial on 150 Ghanaian myopic children aged 10 to 15 years, with mean baseline myopia of −1.98 to −0.50 D. The children were randomly assigned to wear either full‐correction (n = 75) or +0.50 D under‐correction (n = 75) single vision spectacle lenses. An open‐field autorefractor was used to obtain refraction data and ocular biometry results were determined using A‐Scan ultrasonography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al 5 found the mean myopic progressions in the full-correction group and under-correction group were −0.68 AE 0.46 D and −0.64 AE 0.44 D, respectively, at one-year follow-up. In the results of Koomson et al, 6 the mean myopic progressions in the fullcorrection and under-correction groups were −0.54 AE 0.26 D and −0.50 AE 0.22 D, respectively, at the end of 24 months.…”
mentioning
confidence: 86%